The therapeutic potential of apigenin against atherosclerosis - Xueqiang Jiang; Huimin Huang (Heliyon, 2025)
Apigenin is a natural flavonoid abundantly found in fruits, vegetables, and medicinal plants. It possesses protective effects against cancer, metabolic syndrome, dyslipidemia, etc. Atherosclerosis, a chronic immune-mediated inflammatory disease, is the underlying cause of coronary heart disease, stroke, and myocardial infarction. Numerous in vivo and in vitro studies have shown a protective effect of apigenin against atherosclerosis, attributed to its antioxidant and anti-inflammatory properties, as well as its antihypertensive effect and regulation of lipid metabolism. This study aimed to review the effects and mechanisms of apigenin against atherosclerosis for the first time. Apigenin displays encouraging results, and this review confirms the potential value of apigenin as a candidate medication for atherosclerosis.